Factors associated with quit attempt and successful quitting among adults who smoke tobacco in Ethiopia: Global Adult Tobacco Survey (GATS) 2016 - Henok S. Demissie (Tobacco Prevention and Cessation, 2022)
Introduction Tobacco is the leading cause of preventable death in the world. Identification of factors associated with quit attempts and successful quitting can help strengthen tobacco cessation programs. In Ethiopia, no prior study of such factors exists. Our aim was to identify factors associated with quit attempts and successful quitting among adults who smoke tobacco in Ethiopia.